(untitled) (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2024)
Regional development is carried out through two approaches, namely the regional approach and the sectoral approach. The sectoral approach is believed to be able to grow the regional economy to achieve comparative and competitive advantages. The agricultural sector is one of the main contributors to the GRDP value in almost all regions of Indonesia. Way Jepara Sub-district depends on the results of the agricultural sector. Based on the RPJMD document, Way Jepara District has 4 (four) superior agricultural commodities. The research objective is to identify superior commodities in order to encourage economic growth in Way Jepara. The data collected is secondary data in the form of commodity production results in 2017-2022. Analysis techniques used Location Quotient, Shift Share and SWOT in strategy formulation. Researchers found that there are three products that are included in the superior classification, namely rice, cocoa and cassava. Development strategies that need to be carried out are improving infrastructure; improving the quality of human resources; and strengthening institutions.